Stress Distribution Around Two Dental Implant Materials with New Designs: Comparative Finite Element Analysis Study - Alhamdani, Faaiz; Rasheed, Khawla H.; Mahdi, Amjed (Indonesian Journal of Dental Medicine, 2021)
Background: The introduction of modified thread designs is one of the research areas of interest in the dental implantology field. Two suggested Buttress and Reverse Buttress thread designs in TiG5 and TiG4 models are tested against a standard TiG5 Fin Thread design (IBS®). Purpose: The study aims to compare stress distribution around the suggested designs and Fin Thread design. Methods: Three dental implant models: Fin Thread design, and newly suggested Buttress and Reverse Buttress designs of both TiG5 and TiG4 models were tested using FEA for stress distribution using static (70N, 0°) and (400N, 30°) occlusal loads. Results: The main difference between the suggested Buttress design and Fin Thread design lies in the overload (400N, 30°) condition. Maximum Von Mises stress is less in Buttress design than Fin Thread design. On the other hand the level of Von Mises stress over the buccolingual slop of the cancellous bone in Fin Thread design liess within the lowest stress level. The suggested Reverse Buttress design, on the other hand showed almost uniform stress distribution in both TiG4 and TiG4 models with maximum Von Mises stress higher than the elastic modulus of cancellous bone in overload (400N, 30°) condition. Conclusion: The suggested TiG4 Buttress design might have a minor advantage of stress level in cases of stress overload. In contrast, Fin Thread design shows minimal stress over the buccolingual slop of the cancellous bone. The suggested Reverse Buttress design might be more suitable for the D1 bone quality region with the advantage of almost uniform stress distribution